Bridging Indigenous Community: A Participatory Documentary Framework for Community Empowerment - Candida, Jau Emang; Aliffazraie, Jali; Noorhaslina, Senin; Doris, Maying; Hishamuddin, Siri; Joyce, Li Yi Eng; Nurul Iman Nuha, Nasser (https://www.riec.unimas.my/intex25, 2025)
Conventional documentary practices often overlook the potential to empower rural and Indigenous communities, resulting in limited agency, ownership, and authentic representation of their narratives. This disconnection highlights the need for a participatory documentary framework that bridges communities and researchers, transforming filmmaking into a tool for community-led storytelling, cultural preservation, and inclusive development.